Walka Hieronima z herezjami chrystologicznymi w świetle nauczania o Chrystusie zawartym w jego Listach - Łukaszczyk, Michał (Vox Patrum, 2024)
This article describes the Christological heresies found in the Epistles of St Jerome. These are Arianism, Apolinarianism, the heresies preached by the Ebionites and Nazarenes, the heresies professing Docetism and Pelagianism. In the heresies described, the Author of the Vulgate demonstrates not only doctrinal errors, but also defends the orthodoxy of the Christian faith in his writings. The article furthermore points out the important issues in Christology highlighted by the Monk of Bethlehem. It is mainly concerned with the confusion of concepts in Greek and Latin concerning the terms οὐσία and ὑπόστασις, the attempt to restore their proper meaning, the formation of the correct meaning and understanding of the term persona, the pointing out of the dangers of Pelagianism and the linking of it to earlier heresies in order to draw attention to its pernicious effects.